Examen especial al componente de propiedad, planta y equipo de la empresa Sociedad Industrial RELI S.A., período 2022 - Quezada Jumbo, Katherine Jessenia (2024)
ABSTRACT: The research work entitled "Special examination of the property, plant and equipment component of the company Sociedad Industrial RELI S.A., period 2022", was carried out with the objective of verifying the management of tangible assets of the entity, in relation to compliance with current accounting policies and regulations. The study adopted a descriptive and quantitative perspective, using documentary and field sources, the design used is non-experimental since only the variables were analyzed, its study population is the documentation of property, plant and equipment assets of the Industrial Company RELI S.A.; the techniques used include observation and survey with their respective instruments. The results revealed significant findings for the organization, due to the great challenges facing the management of its tangible assets, mainly due to the lack of clear procedures and deficient systems to control, maintain and manage property, plant and equipment. Key words: Management, Special review, policies, property, plant and equipment.